Brake squeal of a high-speed train for different friction block configurations. (1st January 2021) - Wu, Y.K.; Tang, B.; Xiang, Z.Y.; Qian, H.H.; Mo, J.L.; Zhou, Z.R.
Abstract: In this work, the effect of friction block configuration on the brake squeal of a high-speed train is investigated. Three friction block configurations of simplified brake pads are used in the brake tests. The test results indicate that friction block configuration has a significant effect on the noise performance of the brake system. Finite element analysis reveals that the break squeal occurs due to the mode coupling of the brake system. Different friction block configurations lead to different mode characteristics, contact behaviors, and noise performances. Moreover, a full-scale finite element model of the high-speed train brake system is established. The simulation results show that the friction block configuration with a relatively even distribution of the interfacial contact pressure has a relatively lower squeal propensity. Therefore, adjustment of the friction block configuration is an efficient method for noise reduction of railway brakes.